Ecophysiological aspects of some sweet cherry cultivars from the North-East of Romania - Iulia Mineata; Ionel Perju; Sorina Sîrbu; Iuliana Elena Golache; Ionut Vasile Ungureanu; Stefanica Ostaci; Carmen Doina Jitareanu (Horticultural Science)
The physiological performance, growth and competitive ability of fruit trees are increasingly affected by the effects of global climate change, very different at a regional level, which mainly causes considerable changes in water availability. The purpose of this study was the evaluation of three sweet cherry cultivars from the Research Station for Fruit Growing (RSFG) Iași, Romania under the climatic conditions of 2022-2023 by performing physiological investigations into the water regime and the transpiration process through the stomatal conductance, the water content of the leaves as well as their dehydration rate after 24 hours. The obtained data were statistically interpreted taking three experimental factors into account: factor A consisted of three distinct phenological stages (full flowering, fruit about 80% of the final size and fruit ripening); factor B constituted by the three cultivars ('Van', 'Andreiaș' and 'Margonia'); and factor C was constituted by the canopy area from the samples (internal and external). The experimental variants statistically interpreted by Duncan's test (P ≤ 0.05) registered significant differences. The Pearson correlation coefficient (R2) between the measured variables obtained positive distinctly significant values of R2 = 0.686 (with the stomatal conductance) and negative distinctly significant values of R2 = -0.874 (with the water content). The obtained results will support the development of predictive models for different irrigation and breeding strategies to improve the sweet cherry production in temperate continental climates.